The relationship between leg muscle strength and dynamic balance in skateboard players - Ni Made Arindra Widyaswari; I Dewa Gede Alit Kamayoga; Agung Wiwiek Indrayani; Anak Ayu Nyoman Trisna Narta Dewi (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Skateboarding is a sport that utilizes a wheeled board as its equipment. As time progresses, skateboarding has evolved into one of the branches of professional sports, even having official competitions. It is popular among a wide range of young people and adults. Skateboarders must have good balance to stabilize their bodies and minimize the risk of falling and injury. It is maintaining balance while skateboarding requires strength in leg muscles, including flexors, extensors, dorsiflexors, plantar flexors, invertors, and evertors, with proper contraction ratios to stay balanced. The researchers aimed to investigate the relationship between leg muscle strength and dynamic balance in skateboard players. Skateboard players with greater leg muscle strength tend to maintain their balance better when performing tricks and maneuvers on the skateboard. Methods: The research was observational analytics with a cross-sectional approach. Purposive sampling was employed to select participants, resulting in a sample size of 51 skateboarders. Data collection involved measuring leg muscle strength and dynamic balance. Leg muscle strength was measured using a leg dynamometer, while dynamic balance was assessed using the y balance test. Results: The results showed a relationship between leg muscle strength and dynamic balance in skateboarders. Most samples exhibit muscular leg muscle strength, leading to a favorable dynamic balance. Conclusion: From the research findings, it can be concluded that there is a strong, significant, and inverse relationship between leg muscle strength and dynamic balance in skateboarders.